The advantages and disadvantages of biodentine: satisfactory mechanical properties and radiopacity not meeting ISO standard - Milutinović-Smiljanić, Sanja; Ilić, Dragan; Danilović, Vesna; Antonijević, Djordje (Vojnosanitetski pregled, 2021)
Background/Aim. In dentistry, the concept of using inert materials for tissue repair has been replaced by the strategy to find bioactive materials which positively interact with human tissues. The aim of this study was to characterize the physicochemical properties of the commercially available calcium silicate and calcium carbonate-based dental cement, biodentine (Septodont, France). Methods. Material elucidation included the measurements of radiopacity, scanning electron microscopy and x-ray dispersive analyses, wettability, Fourier transform infrared spectroscopy, microindentation, micro- to nanoporosity, setting time, pH and calcium ion release. The cells (mouse bone marrow mesenchymal stem cells – BMSCs) were grown on biodentine surface in order to evaluate its behaviour under biological conditions. Results. The radiopacity of the cement (2.8 mmAl) was below ISO requirement for a root canal filling material. The cement was composed of fine powder with particles similar in size and shape, changing from oval to cubic after having been soaked in a simulated body fluid. Biodentine demonstrated good micromechanical properties and low porosity attributed to microporosity with the average pore size of 92 μm. Wettability (contact angle = 41°), calcium ion release (0.098 μg/cm²) and pH of storage solution (9.07) showed satisfactory characteristics. The BMSCa in intimate contact with cement particles remained viable, indicating biodentine good biocompatibility. Conclusion. Biodentine exhibits good mechanical and physicochemical characteristics, but possesses insufficient radiopacity.